Pregnancy complications and risk of uterine rupture among women with singleton pregnancies in China - Jing Tao; Yi Mu; Peiran Chen; Yanxia Xie; Juan Liang; Jun Zhu (BMC, 2022)
Abstract Background The goal of this study was to investigate whether pregnancy complications are associated with an increased risk of uterine rupture (UR) and how that risk changes with gestational age. Methods We obtained all data from China's National Maternal Near Miss Surveillance System (NMNMSS) between 2012 and 2018. Poisson regression analysis was used to assess the risk of UR with pregnancy complications (preeclampsia, gestational diabetes mellitus, placental abruption, placenta previa and placenta percreta) among 9,454,239 pregnant women. Furthermore, we analysed the risks of UR with pregnancy complications in different gestational age groups. Results The risk of UR was increased 2.0-fold (1.2-fold to 2.7-fold) in women with pregnancy complications (except for preeclampsia). These associations also persisted in women without a previous caesarean delivery. Moreover, an increased risk of UR before term birth was observed among women with gestational diabetes mellitus, placental abruption and placenta percreta. The risk of UR was slightly higher in women with gestational diabetes mellitus who had a large for gestational age (LGA) foetus, especially at 32 to 36 weeks gestation. Conclusions The risk of UR is associated with gestational diabetes mellitus, placental abruption, placenta previa and placenta percreta, but varies in different gestational ages.